Optical magnetism in planar metamaterial heterostructures - Georgia T. Papadakis (Nature Portfolio, 2018)
Most natural materials do not have a magnetic response at optical frequencies and inducing optical magnetism by metamaterials typically requires complex nanostructures. Here, Papadakis et al. show that artificial optical magnetism can also be achieved with planar multilayer metamaterials.